The effect of circulating tumor DNA on the prognosis of patients with head and neck squamous cell carcinoma: a systematic review and meta-analysis - Ruoyi Yang; Teng Li; Sicheng Zhang; Chunyan Shui; Hong Ma; Chao Li (BMC Cancer)
Abstract Background Circulating tumour DNA (ctDNA) has emerged as a valuable liquid biopsy biomarker in the field of oncology, including head and neck squamous cell carcinomas (HNSCCs), offering potential insights into cancer diagnosis, progression, and prognosis. This review aims to comprehensively evaluate the utility of ctDNA as a prognostic biomarker in HNSCC. Methods PubMed and Ovid were searched as part of our review. Studies that investigated the relationship between ctDNA and prognosis in HNSCC patients were included. Outcomes extracted included basic characteristics, ctDNA details and survival data. Meta-analysis was performed on eligible studies to determine pooled progression-free/recurrence-free survival (RFS/PFS) and overall survival (OS). Results Twenty-two studies were included, involving 5062 HNSCC patients from 11 countries. The meta-analysis demonstrated that the positive ctDNA/methylation detection was associated with worse OS (HR = 2.00, 95% CI 1.35–2.96) and worse PFS/RFS (HR = 3.54, 95% CI 1.05–11.85). Positive ctEBV DNA was associated with poorer OS (HR = 2.86, 95% CI 1.84–4.45) and poorer PFS/RFS (HR = 1.93, 95% CI 1.74–2.13). Positive ctHPV DNA was associated with poorer OS (HR = 1.38, 95% CI 1.07–1.38) but not PFS/PFS (HR = 1.33, 95% CI 0.96–1.85). Conclusion Meta-analysis indicates that the status of ctDNA is significantly associated with the prognosis of HNSCC patients, with ctDNA/methylation-negative patients demonstrating better PFS/RFS and OS.